Analysis of Leadership Style at the National Amil Zakat Agency (BAZNAS) Sumedang - Solihin Royani; Cristi Monica Cahyadi (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2022)
The focus of this study aims to see how the application of leadership style in the Sumedang District BAZNAS, the dimensions of the Leadership Style used are five dimensions, the first dimension is nature, the second dimension is habit, the third dimension is temperament, the fourth dimension is character, and the fifth dimension namely personality. This type of research used by researchers is descriptive qualitative, data that has been collected and then performed data reduction is summarizing and selecting data, then presenting data, then finally drawing conclusions so that it provides a complete description and a true picture. The informants of this study are Deputy Chair 1, Public Relation and Information Services, Financial Coordinator, Executor Implementer. Pengindustrian & pendayagunaan. The results of the research on the leadership style of the Sumedang District BAZNAS were categorized quite well based on the five dimensions used, the leadership style in the Sumedang District BAZNAS included in the Humanistic Leadership Style, seen from the communicative leadership nature so that it has a very good relationship with employees, then decision making use the road of deliberation, consensus, and the leadership is always open to employees in terms of receiving input or suggestions from employees. It can be concluded that the application of leadership style in the BAZNAS of Sumedang Regency is appropriate, and for suggestions to be further enhanced on the concept of commitment and consistency from the leadership